Cultural Determinants of Modern Education and Inculcation of Universal Values in Students - A. Osiptsov (Евразийская интеграция: экономика, право, политика, 2019)
The article deals with the solution of such urgent problems as the development and inculcation of human values in today’s youth. It analyzes the scientific publications of domestic and foreign scholars devoted to the problem of value orientations and the formation of spiritual and moral and ethical cultural needs of individuals and society as a whole.